Inventory Procurement Strategy of Product Ingredients in Canned Tuna Industry - Sirawathanakhul, Pheeraphat; Somboonwiwat, Tuanjai (Thai Industrial Engineering Network Journal, 2020)
Inventory procurement of product ingredients in canned tuna industry is purchased independently resulting in wasted cost and deteriorating ingredients. Therefore, this research is developed for strategic improvement of procurement and management of several product ingredients from same supplier to minimize inventory cost by adopting the Applied Economic Order Quantity (EOQ) methodology. The 3 models of Applied EOQ are independently order individual item, jointly order for all items, and partially jointly order for selected items varied by order. The improvement of inventory management with simulated model show partially jointly order for selected items varied by order model can reduce inventory cost by 30%.